(untitled) - Juliana Nunes Maciel Cilento; Neusa Yuriko Sakai Valente (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: Weathering nodules of the ear are pale yellow, asymptomatic lesions which predominate on the helices of the ears. Although their pathogenesis remains unknown, there is an association with chronic exposure to ultraviolet radiation, age and thermal injuries. Few studies have been conducted to date, and these involved a very small number of patients. OBJECTIVE: Study the prevalence of weathering nodules of the ear in patients treated in the Dermatology Service of the State Civil Servant's Hospital of São Paulo, and evaluate their probable relationship with sun exposure, age and phototypes I and II. METHODS: Four hundred patients older than 20 years of age were examined between July 2008 and December 2008. A questionnaire evaluating age, sex, place of birth, origin, occupation and history of sun exposure was applied. All patients were examined and evaluated for the presence of lesions by only one person. RESULTS: The data showed that 155 (38.8%) patients had a lesion in at least one of the ears. The Chi-Square Test was used for the comparative analysis between the groups of patients with and without lesions. In the group of patients with lesions, 29% were 70 to 79 years old, 78.1% had a history of sun exposure and 45.1% belonged to FITZPATRICK skin phototypes I and II (p<0.05%). CONCLUSION: The findings suggest relevant prevalence, probable association with chronic sun exposure, advanced age and phototypes I and II. FUNDAMENTOS: Pápulas climáticas das orelhas são lesões assintomáticas de coloração amarelo-pálida que predominam na hélice das orelhas. Sua patogênese permanece desconhecida, no entanto é descrita a associação com exposição crônica à radiação ultravioleta, idade e injúrias térmicas. Poucos estudos foram realizados até o momento e os mesmos envolveram número muito reduzido de pacientes. OBJETIVO: Estudar a prevalência de pápulas climáticas das orelhas nos doentes atendidos no Serviço de Dermatologia no Hospital Servidor Estadual de São Paulo e avaliar a provável relação com exposição solar, idade e tipo de pele. MÉTODOS: Foram examinados 400 pacientes com idade superior a vinte anos no período compreendido entre os meses de julho de 2008 a dezembro de 2008. Foi aplicado questionário que avaliou idade, sexo, naturalidade, procedência, profissão e história de exposição solar Todos os sujeitos da pesquisa foram examinados por um único observador e avaliados quanto à presença de lesão. RESULTADOS: Os dados revelaram que 155 (38,8%) pacientes apresentavam lesão em pelo menos uma das orelhas. Foi utilizado o teste do Qui-Quadrado para análise comparativa entre o grupo de pacientes com e sem lesão. No grupo de pacientes com lesão 29% tinham idade entre 70 e 79 anos, 78,1% tinham história de exposição solar e 45,1% pertenciam ao fototipo I e II da classificação de FITZPATRICK (p<0,05%). CONCLUSÃO: Os achados sugerem prevalência relevante, provável associação com exposição solar crônica, idade avançada e com o fototipo I e II.